Südost-Forschungen : Internationale Zeitschrift für Geschichte, Kultur und Landeskunde Südosteuropas (Oldenbourg Wissenschaftsverlag, 2015)
The focus of this interdisciplinary journal is on the history of Southeast European cultures. It also publishes papers on Southeast European geography, art, literature, religious studies, economy, linguistics, and ethnology. In its extensive reviews section, Südost-Forschungen offers a broad overview of the current academic literature in all relevant languages.